The case for Ağrı Dağı/Masis as Biblical Mt. Ararat - Younker, Randall W.
While there have been several proposals for the location of the ark of Noah’s landing place, the two most widely accepted have been Mt. Judi and Ağrı Dağı/Masis.1 Of these two, Mt. Judi has received the greater support among scholars. One of the main arguments in support of Mt. Judi is that it is the older tradition (3rd century B.C.), while the tradition that Ağrı Dağı/Masis is the Biblical Mt. Ararat is said to have originated late—only in the 12th century A.D. or there about. In this paper we will make the case that the tradition for Ağrı Dağı/ Masis is actually the older tradition and is in the region of Ararat the Biblical author of Genesis 8:4 had in mind. We will use two main arguments. First, the tradition that Ağrı Dağı/Masis is a sacred, cosmic mountain is very ancient, going back to at least the 22nd century B.C. Second, that by looking at the flood accounts of Mesopotamia in tandem with the Hebrew account, it can be seen that while not naming the specific location, the Hebrews understood the ark to have landed in the vicinity of Ağrı Dağı/Masis–not in the region of Mt. Judi (or other proposed sites). This is because the term “mountains of Ararat” (Urartu) had a more restricted geographic range at the time the Biblical writer wrote.